Multifocal brown tumour associated with parathyroid adenoma - KC, Sudeep; Paneru, Manisha; Yadav, Deepak; Shrestha, Manisha (Journal of Patan Academy of Health Sciences, 2024)
Brown tumors are focal lytic bone lesions associated with primary or secondary hyperparathyroidism. In the present era, brown tumors causing multiple lytic bone lesions are rare due to the early detection of hyperparathyroidism through biochemical investigations and effective treatment. We report a case of a 30-year-old woman initially thought to have a bone tumor in her tibia, but further radiological and biochemical investigations revealed primary hyperparathyroidism with multiple brown tumors. This case emphasizes the importance of using imaging techniques to accurately diagnose and treat uncommon conditions like brown tumors in cases of primary hyperparathyroidism.